Associations between employment status, type of occupation, and mental health problems in a treatment seeking sample - Lundqvist, Jakob; Lindberg, Martin S.; Brattmyr, Martin; Havnen, Audun; Hjemdal, Odin; Solem, Stian (Frontiers in Psychology, 2025)
BackgroundPrevious studies have not investigated psychological profiles across different types of occupations and unemployment in samples seeking mental health treatment.AimsThe main aim of the study was to explore associations between employment status, type of occupation, and mental health problems in a clinical sample.MethodsThe sample consisted of 2014 participants seeking treatment at a community mental health service. Employment status and type of occupation were compared with the general Norwegian population. Logistic regression analyses (adjusting for age, sex, household income, and relationship status) explored associations between mental health (use of psychotropics, alcohol, depression, anxiety, work- and social functioning, and general health), employment status, and type of occupation.ResultsUnemployed participants, individuals on work assessment allowance/other benefits, and clerical workers were overrepresented in the sample. People receiving disability benefits or work assessment allowance showed higher use of psychotropic medication, reported more anxiety and depression, and lower functioning and health. There were some significant differences between specific occupations, but these effects were relatively small.ConclusionThe findings suggested that type of occupation was less relevant to mental health outcomes, whereas different types of unemployment was clearly associated with worse mental health. Future research should address treatments integrating mental health focus along with work focus.